Favoured instructional methods and teaching materials for Online Distance Learning (ODL) lectures on interactive multimedia course / Naemah Abdul Wahab ... [et al.] - Abdul Wahab, Naemah; Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina Mohd Mydin; Mohamed Yusoff, Syarifah Adilah (Unit Penerbitan JSKM, 2021)
Computer subjects such as Interactive Multimedia is an important supplementary skill for higher education students in any field of study. Nevertheless, teaching and learning computer subject for non-computer background novice learners using online mode in the midst of COVID-19 pandemic is very challenging. Thus, this study was done to identify the technical issues and difficulties, favoured approaches for lectures, exercises and reference materials as well as preferred platform for lecture classes to be conducted using Online Distance Learning (ODL). This study was conducted at the Department of Computer and Mathematical Sciences, Universiti Teknologi MARA Cawangan Pulau Pinang. An online questionnaire via google form was created to collect data from 91 students. The findings will be used to enhance the online lectures teaching technique for CSC253 course in the upcoming semesters, increase students ' understanding and interest in this subject along with improving students ' grade.